The Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Hazareshwar Temple is a small structure, in contrast to the Mahakal and Undeshwar temples, with a mandapa (pillared hall), antarala (vestibule), and garbhagriha (sanctum sanctorum).